The importance some clinical factors with estimation of immunological biomarkers (interleukin IL-1B, IL-6, IL-10 and INF-ɤ) in breast cancer (Damascus University Journal for engineering sciences, 2022)
Background and aim:   The correlation between age groups, body mass index and cancer grade with serological concentrations of immunological biomarkers (interleukin IL-1B, IL-6, IL-10 and INF-ɤ) among females with breast cancer was carried out in this study.Methods: The total number of breast cancer patients involved in this study are (80) individual were taken from Basrah oncology center in  Basrah province, the age of patients range from 27-76 yrs and (80) individuals considered as control group after they were checked and confirmed to be free from any chest or any other health problems.Results: The levels of interleukin IL-1B, IL-6, IL-10 and INF-gamma (pg/ml) were determined among patients with breast cancer and control groups in various age groups, stages of breast cancer and various body mass indices . Conclusion: there are statistical correlation between various clinical factors and various stages of breast cancer
Keywords: breast cancer, cancer grade; BMI; age group; IL-1B, IL-6; IL-10 and INF-ɤ, statistical analysis